Miniature Specimen Fracture Toughness Testing: A Concise Review - Azhar, Muhammad Asyraf (Universiti Sains Malaysia, 2022)
The miniature fracture toughness was done as many issues are brought out, and one main factor of those is limited available material. The miniature fracture toughness could provide useful information related to the properties of the material with only use small part of the material. The thesis provides a technical review of miniature fracture toughness testing, standardization, and evaluation for metallic materials. The review discusses the key fracture mechanics parameters for miniature specimen, J-integral, starting with their fundamentals, and definitions and progressing through the experimental estimation, test procedures, and ASTM standardization procedures. Guidelines for selecting a suitable fracture parameter to describe the material's fracture toughness are discussed, as well as instructions for measuring the value of fracture toughness defined in a format of resistance curve using laboratory compact tension specimens. A combined common test standard E1820 for determining J parameters is the applicable ASTM fracture toughness test standard taken into account in this work. The method and technique are also discussed in this paper, including the elastic unloading compliance method and data evaluation and reduction in determining the J – R curve and estimation of JQ. The review also includes the early studies and most recent advancements in fracture toughness test techniques and procedures created by the American Society for Testing and Materials (ASTM). The miniature fracture toughness testing is reviewed in this thesis with following ASTM E1820 standard and gave satisfactory results without utilize large panel specimen.